Factors That Affect Employee Engagement of Bank AAA - Paulus Rega Runtu; Martinus Tjhia Tjen Jong (Institute of Computer Science (IOCS), 2021)
The goal of this study is to analyze the positive impact from organization culture, job satisfaction, and job training to employee engagement of Bank AAA. The survey done by online questionnaire where this research is collecting sample of Bank AAA’s employee. The data analysis approached by PLS-SEM method by using Smart PLS 3.0. The result of this research are organization culture, job satisfaction, and job training positively affects the employee engagement of Bank AAA positively.